The Impact of Profitability Ratios on Islamic Bank Stock Prices: Evidence from the Indonesia Stock Exchange - Fauzi Arif Lubis; Nurwani Nurwani; Mifta Hayani (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study investigates the effect of profitability ratios on the stock prices of Islamic banks listedon the Indonesia Stock Exchange (IDX) during the period 2018–2020. The research employs aquantitative approach using secondary financial data derived from the annual reports of threeIslamic banks, namely Bank BRI Syariah, Bank Panin Dubai Syariah, and Bank BTPN Syariah.Profitability is measured through Return on Assets (ROA), Return on Equity (ROE), and Earningsper Share (EPS), while stock price serves as the dependent variable. Data are analyzed usingmultiple linear regression and classical assumption tests to ensure the validity of results. Thefindings reveal that EPS has a positive and significant influence on stock prices, whereas ROAand ROE show positive butstatistically insignificant effects. Simultaneously, all three profitabilityindicators collectively exert a significant impact on the stock prices of Islamic banks. Theseresults suggest that investors in Indonesia’s Islamic capital market place greater emphasis onearnings information as a reliable signal of firm performance. The study contributes to thegrowing literature on Islamic finance by offering empirical evidence from emerging marketconditions and provides insights for investors, bank managers, and policymakers seeking toenhance financial transparency and market confidence in the Islamic banking sector